2010
DOI: 10.1007/s11630-010-0193-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of choked flows through a convergent nozzle

Abstract: When sonic nozzles of significantly smaller diameter are used as standard flow meters, the critical back pressure ratio is affected by the boundary layer at the nozzle throat. However, the effect of the boundary layer on choking criteria is still controversial. Then, the choking phenomenon of a convergent nozzle flow has been experimentally investigated using four convergent nozzles with the same diameter followed by a straight pipe of a variable length.As a result, it is shown that the critical back pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 3 publications
0
15
0
1
Order By: Relevance
“…3 and 4) predicted with the code and experiment [4]. Static pressure measurement positions (x/D) are shown in Fig.…”
Section: Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…3 and 4) predicted with the code and experiment [4]. Static pressure measurement positions (x/D) are shown in Fig.…”
Section: Validationmentioning
confidence: 99%
“…However, interestingly, it is observed that the flow Mach number exceeds unity near the exit of the straight pipe and hence the flow chokes not at the pipe exit but well upstream of it. In addition, the critical pressure ratio predicted from the experiment is less than the ideal value [4]. In the present effort a large number of simulations are done with different L/D ratios to understand such flows near the pipe exit.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The thickness of the boundary layer formed on the channel wall is thin comparing with the channel size and the flow can be considered as one dimensional flow. However, Kubo et al (2010) measured the total pressure at the outlet plane for a tube of 15 mm in diameter. They reported that the flow velocity at the outlet plane of a straight millimeter sized channel exceeds the speed of sound.…”
Section: Introductionmentioning
confidence: 99%